2017
DOI: 10.1590/1809-4392201602104
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization and compatibility among genotypes to select elite clones of cupuassu

Abstract: The expansion of the genetic base of cultivated materials is an ongoing activity of the cupuassu (Theobroma grandiflorum) breeding program. However, the parents involved need to be genotypically and phenotypically characterized to ensure compatibility of crossings, as well as to assist in the selection of more promising individuals for hybridization. This study aimed to identify and select T. grandiflorum clones that are compatible and genetically divergent using tools such as the estimates of genotypic, pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
3
7
0
2
Order By: Relevance
“…Superior accessions with desirable end-user attributes from these diverse genetic groups are a source of rare alleles for incorporation into elite breeding lines thereby maximizing heterosis in the progenies. The high and moderate correlations observed between the combined matrix and the genotypic and phenotypic dissimilarity matrices, respectively agree with the findings of Alves et al 19 , 22 who dissected genetic diversity in their studies using phenotypic, genotypic and combined distances. These correlations suggest that genetic diversity assessment employing the combined matrix could be an essential tool to capture phenotypic and genotypic information cumulatively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Superior accessions with desirable end-user attributes from these diverse genetic groups are a source of rare alleles for incorporation into elite breeding lines thereby maximizing heterosis in the progenies. The high and moderate correlations observed between the combined matrix and the genotypic and phenotypic dissimilarity matrices, respectively agree with the findings of Alves et al 19 , 22 who dissected genetic diversity in their studies using phenotypic, genotypic and combined distances. These correlations suggest that genetic diversity assessment employing the combined matrix could be an essential tool to capture phenotypic and genotypic information cumulatively.…”
Section: Discussionsupporting
confidence: 89%
“…As a result of the strong environmental influence on their expression, phenotypic markers may not precisely capture the available diversity in a population 7 , 17 . Molecular markers, particularly SSR and SNPs have been widely employed to study the diversity in many species with much success, however, very low or negligible correlations have been reported between the dissimilarity matrices from the genotypic and phenotypic data 18 , 19 . Hence, it suggests that the non-overlapping information is emanating from the phenotypic and genotypic dissimilarity matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Ex Spreng. 12 and Plukenetia volubilis L. 29 . However, they should be excluded from the analyses, because they may lead to false biological interpretations and errors in the genotype selection process, due to the lack of precision in parameter estimation.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design was in randomized blocks with 25 treatments, having five replicates and three plants per plot. At first, clones selected from the Germoplasm Active Bank were hybridized (Alves et al, 2017) by using the cupuassu controlledpollination technique, as reported by Venturieri & Ribeiro Filho (1995). After evaluating and selecting the progenies, the most productive parents, who remained asymptomatic for M. perniciosa after 15 years of field exposure, were duly identified and selected.…”
Section: Methodsmentioning
confidence: 99%
“…In the following crosses, it is important that the used genotypes are genetically distant and compatible. The compatibility rate is found by the ratio between the number of pollinated flowers and the number of fruit, so that when the setting rate is above 30%, it is considered compatible (Alves et al, 2017). The triple-cross progenies used in the present study were obtained in this manner and were constituted by the genetic contributions of three distinct genotypes.…”
Section: Methodsmentioning
confidence: 99%